2016
DOI: 10.1371/journal.pone.0166611
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Bunyavirus-Associated Severe Fever with Thrombocytopenia Syndrome: A Community-Based Case-Control Study

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus. Previous studies about risk factors for SFTSV infection have yielded inconsistent results, and behavior factors have not been fully clarified.MethodsA community-based, 1:4 matched case-control study was carried out to investigate the risk factors for SFTS in China. Cases of SFTS were defined as laboratory-confirmed cases that tested positive for real-time PCR (RT-PCR) for severe fever wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…SFTS has also been reported in South Korea and Japan [6, 7]. There is no licensed vaccine or therapeutic against SFTSV currently, and avoiding tick exposure is an important way to prevent SFTSV infection [8, 9]. The disease was listed as 1 of the 9 infectious diseases on the World Health Organization priority list in 2017 because of a substantial risk to public health [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SFTS has also been reported in South Korea and Japan [6, 7]. There is no licensed vaccine or therapeutic against SFTSV currently, and avoiding tick exposure is an important way to prevent SFTSV infection [8, 9]. The disease was listed as 1 of the 9 infectious diseases on the World Health Organization priority list in 2017 because of a substantial risk to public health [10].…”
mentioning
confidence: 99%
“…Exposure to and bites from infected ticks are thought to be the primary transmission route of SFTSV [8, 9], and secondary cases can be caused by human-to-human transmission, probably through inhalation of virus-containing aerosol [19] and direct contact with blood or bloody secretions bearing SFTSV [20, 21]. The natural foci are thus the basis for the survival, sustaining, and transmission of SFTSV, constituting a potential epidemiological danger.…”
mentioning
confidence: 99%
“…Although viral hemorrhagic fevers commonly occur with etiologyundetermined thrombocytopenia in critically ill patients (TCIP) [1][2][3][6][7][8][9], its relationship to bleeding is not clearly determined because thrombocytopenia is typically mild to moderately severe and it alone can't be accountable for the severe hemorrhagic disorder. Thus, thrombocytopenia has not entered as a serious issue in caring of viral hemorrhagic fevers other than platelet transfusion to maintain it at a safe level.…”
Section: Thrombocytopenia In Viral Hemorrhagic Fevers (Tcip)mentioning
confidence: 99%
“…Previous studies have demonstrated that people who work outdoors and/or live in mountainous or hilly rural areas were considered as a high-risk population and preventative measures that reduce exposure to ticks can prevent SFTSV infection [79]. Owing to the unavailability of vaccines against SFTS and the fatal outcomes of the syndrome, considerable attention should be paid to promoting and strengthening health education and behavioral change among high-risk populations, especially for people who work outdoors in the SFTS endemic areas.…”
Section: Introductionmentioning
confidence: 99%